Tolerogenic effects of 1, 25-dihydroxyvitamin D on dendritic cells involve induction of fatty acid synthesis. Issue 211 (July 2021) - Garcia, Amadeo Muñoz; Bishop, Emma L.; Li, Danyang; Jeffery, Louisa E.; Garten, Antje; Thakker, Alpesh; Certo, Michelangelo; Mauro, Claudio; Tennant, Daniel A.; Dimeloe, Sarah; Evelo, Chris T.; Coort, Susan L.; et al.
Graphical abstract: Highlights: Dendritic cells (DC) treated with 1, 25-dihydroxyvitamin D (1, 25D) alone show a tolerogenic DC phenotype. 1, 25D-treated DC show altered oxidative phosphorylation and electron transport. 1, 25D-treated DC show altered glycolysis and TCA cycle metabolism. TCA effects of 1, 25D enhance fatty acid synthesis by DC. Fatty acid synthesis appears to be essential for DC tolerogenic effects of 1, 25D. Abstract: The active form of vitamin D, 1, 25-dihydroxyvitamin D (1, 25D) is a potent regulator of immune function, promoting anti-inflammatory, tolerogenic T cell responses by modulating antigen presentation by dendritic cells (DC). Transcriptomic analyses indicate that DC responses to 1, 25D involve changes in glycolysis, oxidative phosphorylation, electron transport and the TCA cycle. To determine the functional impact of 1, 25D-mediated metabolic remodelling, human monocyte-derived DC were differentiated to immature (+vehicle, iDC), mature (+LPS, mDC), and immature tolerogenic DC (+1, 25D, itolDC) and characterised for metabolic function. In contrast to mDC which showed no change in respiration, itolDC showed increased basal and ATP-linked respiration relative to iDC. Tracer metabolite analyses using 13 C -labeled glucose showed increased lactate and TCA cycle metabolites. Analysis of lipophilic metabolites of 13 C-glucose revealed significant incorporation of label in palmitate and palmitoleate, indicating that 1, 25D promotes metabolic fatty acid synthesis in itolDC. Inhibition of fatty acid synthesis in itolDC altered itolDC morphology and suppressed expression of CD14 and IL-10 by these cells. These data indicate that the ability of 1, 25D to induce tolerogenic DC involves metabolic remodelling leading to synthesis of fatty acids.